PENGARUH PROPORSI EKSTRAK DAUN KEMANGI (Ocimum basilicum) DAN MINYAK JARAK (Castor Oil) TERHADAP SIFAT ORGANOLEPTIK KONDISIONER - Nadila Setiawati; Sri Dwiyanti; Mutimmatul Faidah; Dindy Sinta Megasari (Program Studi Pendidikan Tata Rias, 2024)
Basil leaf extract (Ocimum basilicum) and castor oil (Castor Oil) have potential as hair conditioner ingredients due to their content of flavonoids, alkaloids, saponins, tannins, and fatty acids. This study aims to evaluate the effect of the ratio of these two ingredients on the organoleptic characteristics of the conditioner, including color, aroma, and panelists' preference. The method used is an experiment with independent variables consisting of the ratios of basil leaf extract and castor oil: X1 (0.5g:3.5g), X2 (1g:4g), and X3 (1.5g:4.5g). Data were collected through observations by 30 panelists and analyzed using single variance analysis and Duncan's test with SPSS 29 software. The results indicate that the ratio of basil leaf extract and castor oil significantly affects the aroma and preference of the panelists. The best combination is a conditioner with a ratio of 1g basil leaf extract to 4g castor oil.